P3-S7.15 Diagnostic reliability of wet prep microscopy for T Vaginalis in women visiting a high-volume STD clinic. (10th July 2011) - Fitch, J; Anderson, T; Thrun, M; Mettenbrink, C
Abstract : Background: For years, wet prep microscopy has been the cornerstone of testing for T vaginalis due to the simplicity of the test and its low cost to perform. Though still recommended as a means of diagnosis for vaginal infections, its diagnostic sensitivity (typically 50%–70%) falls short of other means of testing, including culture (approximately 80% sensitivity). This study compares the performance and costs of wet prep tests to culture in the hands of experienced laboratorians in a high volume STD clinic. Methods: The Denver Metro Health (STD) Clinic sees over 800 patients and performs over 100 wet prep tests every month. Between 1 January 2010 and 30 September 2010, a wet prep test and a T vaginalis culture were performed on every female patient receiving a comprehensive exam, regardless of symptoms, as part of resistance testing for the STD Surveillance Network (SSuN). The results of the two tests were then compared. Results: Wet prep tests and T vaginalis cultures were performed on 555 female patients. Of those, 51 were positive by wet prep and 62 were positive by culture see Abstract P3-S7.15 table 1 . There were no wet prep false positives reported. The average material cost for each in-house wet prep was 0.32 and the cost for each culture was 1.78. In comparision, materials for PCR testing for T vaginalis cost approximately 2 per test. Staff time required to perform wet prep microscopy is less than either culture or PCR. Conclusions: The wet prep sensitivity rate of 82.2% when compared to culture (which, until recently has been the gold standard for trich testing) suggests that wet prep microscopy may be more useful than previously recognised in venues where clinicians and laboratorians gain experience by performing a large number of tests. Additionally, the costs, both in supply and staff expense, suggest that, in tight budgetary times, wet prep may continue to be a cornerstone of T vaginalis testing, even with the availability of molecular amplification methods. These results, however, were limited to a single clinic during a single point in time. As next steps, wet prep testing might be compared to molecular amplification tests.